Exploratory study on the potential benefits of prophylactic levetiracetam after acute spontaneous intracerebral hemorrhage - Babi, Marc A.; Lishen, Irina; Louis, Barbara Pierre; Woodbury, Katelyn; Kennedy, Anthony; Abuzeid, Fouad; Nouh, Amre (Frontiers in Neurology, 2025)
ImportanceCurrent guidelines recommend against the routine use of seizure prophylaxis in acute spontaneous intracerebral hemorrhage (sICH).ObjectiveThe goal of this study is to evaluate if the use of prophylactic levetiracetam resulted in reduced incidence of seizure, morbidity, and length of stay, compared to patients who did not receive prophylactic levetiracetam.DesignThis retrospective chart review includes patients admitted with ICH at Cleveland Clinic Florida Martin Health from January 2019 to October 2022.Main outcome and measuresThe primary outcome was the incidence of seizure during the first 7 days of admission. Secondary outcomes include intensive care unit and hospital length of stay, measured in days.ResultsA total of 160 patients were included in this study, 93 in the levetiracetam group. The primary outcome of clinical seizure incidence within 7 days of ICH diagnosis was observed in five patients, all of whom were in the prophylactic levetiracetam group, though this did not reach statistical significance (5% vs. 0%; p = 0.075). In adjusted analysis, levetiracetam showed a non-significant protective trend (OR 0.71, 95% CI 0.13–3.79). The median length of hospital stay and ICU stay were both longer in the prophylactic levetiracetam group (5 days vs. 3 days; p < 0.001 and 2 days vs. 1 day; p = 0.001, respectively). However, in adjusted analyses, these differences were not statistically significant.Conclusion and relevanceThe routine use of seizure prophylaxis with levetiracetam did not result in a significant reduction in early seizure incidence, and in unadjusted analyses, the prophylaxis group had longer ICU and hospital stays. However, these differences were not significant after adjustment for key clinical confounders. Randomized controlled trials need to be conducted to determine whether seizure prophylaxis with levetiracetam contributes to worse outcomes.